1922 — the best year of the Comintern. Soviet Russia, German communists and the Genoa conference - A. Yu. Vatlin (Вестник Московского Университета. Серия XXV: Международные отношения и мировая политика)
The signing of the Declaration on the formation of the Soviet Union on December 30, 1922 marked a new stage in the history of international relations, and, at the same time, took stock of intense domestic and international political struggle unfolding in the previous years. The developments within the Communist International were of particular importance for both the outcomes of this struggle and the future of international labor movement. The author stresses that for the Comintern the year of 1922 was dominated by a struggle between the two opposing ideological and political trends: the inertia of the ‘storm and onslaught’ enthusiasm of the first post-revolutionary years and the rise of the ideas of peaceful coexistence. In this context, the paper assesses the role that the Bolshevik leaders envisaged for the Comintern during the preparation and conduct of the Genoa Conference and, particularly, for the policy of the united workers front. The author shows that the very idea of cooperation with socialists and social democrats received an extremely ambiguous reaction from representatives of Western communist parties. In this regard, the position of the German Communist Party (KPD) was of particular importance to the Bolshevik leaders. Indeed, the case of KPD was emblematic of those tendencies and contradictions that marked the development of the international communist movement in the period under review. The KPD leaders welcomed the Comintern’s turn towards a united workers front. However, the author notes that this support was based on a highly unstable compromise between multiple contradicting domestic and foreign policy imperatives, including opposition from the left-wing radicals within the party and continuous conflict with the government of the Weimar Republic, exacerbated by ideological and financial dependence on Moscow. As a result, the KPD’s actions were very often ad hoc and inconsistent, reflecting general issues typical to the international labor movement of that period. That became clear during the Fourth Congress of the Comintern, which took place at the end of 1922. It failed to outline a clear strategy for interaction between the Russian Bolsheviks and foreign communists. At the same time, the outcomes of the Fourth Congress were crucial for further evolution of the ideology and practical activities of the Comintern. The policy of the united workers front got a broader definition as the Communist International started to recognize the threat posed by fascism.